Relationship between unemployment and inflation in Poland in the context of the Phillips curve — a time of pandemic and war in Ukraine - Anna Ćwiąkała-Małys; Monika Mościbrodzka (Wrocławsko-Lwowskie Zeszyty Prawnicze)
In this article we undertake a verification of the Phillips curve in Polish conditions during the pandemic and the war in Ukraine. The theoretical part introduces evolution of Phillips’s theory and the review of literature and its verification in the conditions of Polish economy. Additionally, theoretical aspects regarding crisis and exogenous shocks are discussed. The aim of the empirical part of the work was to investigate the existence of the Phillips curve in the Polish economy in 2013–2022. The direction and strength of the relationship between inflation and unemployment rates were tested based on monthly data on full period and the pandemic period. In the research econometric methods were used in order to estimate parameters of an autoregressive inflation model, including both the influence of unemployment on the inflation rate and exogenous shock that were caused by periods of economic disruption reflected by binary, sustained and interaction variables. It was concluded that in the pandemic time the effect of the Phillips curve was present and that was accentuated by the war. However, in the longer term, this effect was not perceived as a negative relationship between characteristics under study. Nevertheless, in the full period of the study, disruptions in inflation patterns which were caused by the pandemic and the period of Russian aggression against Ukraine were evident.